Epidemiological characteristics of patients starting chronic hemodialysis in the Alberto Sabogal Sologuren Hospital 2015 - Huamán C., Luis (2016)
Objective: To identify the epidemiological characteristics of patients starting chronic hemodialysis during 2015 in the Alberto Sabogal Sologuren, EsSalud Hospital. Callao, Peru. Material and Methods: Observational and descriptive cross-sectional study. The study population consisted of 30 patients who started chronic hemodialysis therapy in the Alberto Sabogal Sologuren, Hospital EsSalud. Information was obtained through a form developed by the researcher through two sources; medical history and by reference of the same patient and / or family. The main epidemiological variables collected were: personal and clinical data, emphasizing the latter on the previous control in pre dialysis stage, that is, if the patients had some preparation by a team of renal dialysis health professionals for their scheduled entry for dialysis. Results: The mean age was 62.3 years, and 53.3% of patients were older than 60 years. The mode of admission was by emergency: 73.3%, and 13.3% for surgery and hospitalization. The type of access used 86.7% temporary catheter; 10% arteriovenous fistula and 3.3% tunneled catheter. Diabetes and hypertension with 36.7% and 33.3% respectively were the most common causes of CKD. Conclusion: Half of patients, who started hemodialysis were beyond the sixth decade of life and came in poor clinical, gasometry and biochemical conditions. A large proportion of patients admitted for emergency rooms with the consequent negative impact on the economy and survival of patients. The most common vascular access for hemodialysis was the temporary catheter.